Attachment procedure - Chiriac, Paula (Eximia, 2023)
During criminal proceedings, the competent judicial bodies have the authority to order certain procedural measures to guarantee and ensure the normal conduct of proceedings, the execution of the sentence, the regulation of the damage caused by the crime and the prevention of antisocial acts. Preventive, precautionary, safety and immediate redress measures, defined by doctrine as the return of property and restoration of previous condition, are examples of procedural measures that might be required during criminal proceedings. Precautionary measures are procedural, coercive and effective measures taken by judicial authorities to freeze certain movable or immovable property by confiscating it, to prevent the destruction, concealment, theft or disposal of property subject to special or extended confiscation, to ensure enforcement of fines or court costs, or to make good the damage caused by the criminal offence. Confiscation, seizure and attachment are examples of preventive tactics. As for the functionality of precautionary measures, they are only protective, not remedial. Precautionary measures are intended to prevent the concealment, destruction, disposal or theft of property which may be subject to special or extended confiscation or which may be used to enforce fines or court fees or to make good the damage caused by the criminal offence.